The role and mechanism of TXNDC5 in disease progression - Jiao, Mingxia; Zhang, Yeyong; Song, Xie; Xu, Bing (Frontiers in Immunology, 2024)
Thioredoxin domain containing protein-5 (TXNDC5), also known as endothelial protein-disulfide isomerase (Endo-PDI), is confined to the endoplasmic reticulum through the structural endoplasmic reticulum retention signal (KDEL), is a member of the PDI protein family and is highly expressed in the hypoxic state. TXNDC5 can regulate the rate of disulfide bond formation, isomerization and degradation of target proteins through its function as a protein disulfide isomerase (PDI), thereby altering protein conformation, activity and improving protein stability. Several studies have shown that there is a significant correlation between TXNDC5 gene polymorphisms and genetic susceptibility to inflammatory diseases such as rheumatoid, fibrosis and tumors. In this paper, we detail the expression characteristics of TXNDC5 in a variety of diseases, summarize the mechanisms by which TXNDC5 promotes malignant disease progression, and summarize potential therapeutic strategies to target TXNDC5 for disease treatment.